2012
DOI: 10.1143/jjap.51.06fd28
|View full text |Cite
|
Sign up to set email alerts
|

In-situ Observation of Surface Graphitization of Gallium Droplet and Concentration of Carbon in Liquid Gallium

Abstract: Although carbon has been recognized to be insoluble in gallium, we found that the outermost surface of gallium has unexpectedly high carbon solubility, particularly the limited region of about a few nanometers in depth. Our in-situ transmission electron microscope observations revealed that a graphene layer was precipitated at the surface of a gallium droplet simultaneously with gallium evaporation, and some of the droplets created an internal graphitic layer. On the basis of these experimental data, we evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In contrast with previous in situ TEM observations, we do not observe graphitic shell formation around the droplets. 19,21,22,24 We do, however, observe small remnants that do not change in size after the bulk of the droplets dissolve. While the images lack sufficient resolution to identify these features, presumably they are graphitic shells as has been reported in the literature.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…In contrast with previous in situ TEM observations, we do not observe graphitic shell formation around the droplets. 19,21,22,24 We do, however, observe small remnants that do not change in size after the bulk of the droplets dissolve. While the images lack sufficient resolution to identify these features, presumably they are graphitic shells as has been reported in the literature.…”
mentioning
confidence: 52%
“…While carbon is expected to be insoluble in liquid gallium, previous studies have suggested otherwise and due to the large difference in the surface energies, liquid gallium does not wet amorphous carbon and forms droplets with wetting angles exceeding 120 . 19,[21][22][23] In this letter, we present in situ transmission electron microscopy (TEM) studies of the decay behavior of Ga droplets on amorphous carbon thin films during annealing. From the time-lapsed TEM images, we find that smaller droplets shrink and the volume decay rates depend on the local environment, characteristic of surface-diffusion-limited Ostwald ripening.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated previously that the outermost surface of molten gallium can absorb up to 50 wt% of carbon in a ~5 nm thin skin layer 23 , despite a low carbon solubility in gallium. At ~1000 °C, carbon atoms diffusing through bulk liquid gallium is also possible 42 .…”
Section: Resultsmentioning
confidence: 95%
“…Along with the typical metal catalysts for growing graphene (copper and nickel), it is proved that Ga catalyst provides favorable controllability in the layer numbers of graphene because of the lower solubility of carbon . In addition, the saturated vapor pressure of low‐melting‐point Ga is nearly one order of magnitude higher than that of Cu under the same condition, which would provide more catalyst atoms in the graphene growth on insulating substrates .…”
Section: Gaseous‐promotor‐assisted Growth: Metallic Speciesmentioning
confidence: 99%